Media Komunikasi Digital Dapat Meningkatkan Prestasi Belajar Mahasiswa - Ridha, Muhammad; Rubino, Rubino; Kustiawan, Winda (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
This research aims to analyze the use of communication media digital in improving the learning achievement of students in the da'wah faculty and communication Al-Aziziyah Samalanga Bireun Islamic institute . This research uses qualitative research with this type of research field (field research). The informants in this research are leaders and Student at the Faculty of Da'wah and Communication at the Al-Aziziyah Samalanga Bireun Islamic Institute and data collection techniques were carried out by observation, unstructured interviews and documentation related to the discussion on research. Based on the results of this research, it can be concluded that students who actively use digital communication media tend to achieve higher academic achievements. Interactions that occur through digital platforms also help in developing communication skills, mastery of material, and collaboration between students. The digital communication media used is Online Media, including all online platforms, including email, social media, faculty websites, and streaming or video conferencing. Optimizing the use of digital communication media in improving student learning achievement includes, Optimization Objectives, seeking to maximize existing media for use in learning. The Decision Alternative seeks to choose digital communication media in this case to help the teaching and learning process. Resources, in this case developing and creating students who are interactive in learning and creating students who are skilled in using digital communication media. There are several obstacles to the use of digital media in improving student learning achievement at the Faculty of Da'wah and Communication, Al-Aziziyah Samalanga Bireun Islamic Institute, including, Technical Barriers, including Accessibility issues, not all students have the same access to technology. Infrastructure Constraints: Some students may not have adequate devices or internet connections. Human Barriers, including the problem of Lack of Technology Skills. Some students may not be familiar with or lack skills in using complex digital technology. Difficulty concentrating, due to disturbances from the surrounding environment or lack of face-to-face interaction can affect learning focus